2007
DOI: 10.1186/1743-422x-4-10
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the AV2 gene by antisense RNA protects transgenic plants against a bipartite begomovirus

Abstract: Whitefly-transmitted geminiviruses (genus Begomovirus) are phytopathogens that cause heavy losses to crops worldwide. Efforts to engineer resistance against these viruses are focused mainly on silencing of complementary-sense virus genes involved in virus replication. Here we have targeted a virion-sense gene (AV2) to develop resistance against Tomato leaf curl New Delhi virus, a bipartite begomovirus prevalent throughout the Indian subcontinent. We show that tobacco plants transformed with an antisense constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…We show that resistance was acquired by RNA silencing through the production of transgene-specific siRNA. The present study and work reported elsewhere [ 40 , 41 ] suggests that AV1 / AV2 could be targeted to confer resistance to geminiviruses.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We show that resistance was acquired by RNA silencing through the production of transgene-specific siRNA. The present study and work reported elsewhere [ 40 , 41 ] suggests that AV1 / AV2 could be targeted to confer resistance to geminiviruses.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the AV2 protein of tomato leaf curl virus (ToLCV) and tomato yellow leaf curl virus (TYLCV) is shown to act as a potent suppressor of gene silencing activity. Silencing of AV2 gene of ToLCV by antisense RNA [ 40 ] and AV1/AV2 genes of ToLCV by artificial micro RNA [ 41 ] resulted to increased resistance to the virus in transgenic tobacco and tomato, respectively. Moreover, SLCMV DNA A has been reported to have properties of a monopartite begomovirus, which in the absence of DNA B, can induce upward leaf roll and vein swelling symptoms similar to those produced by monopatrtite begomovirus [ 10 ], indicating that the AV2 protein maybe involved in cell-to-cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, V2 encoded by CLCuMV is a very strong suppressor of gene silencing [10]. Tobacco plants were developed harboring an antisense construct targeting the AV2 gene of Tomato leaf curl New Delhi Virus (ToLCNDV) [47]. Upon challenging with virus-infectious clones of ToLCNDV, transgenic plants remained asymptomatic, although viral DNA could be detected by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its structural importance and its role in the folding of knotted proteins, we combined single molecule force spectroscopy and steered molecular dynamics (SMD) simulations to investigate the unfolding mechanism of the slipknotted protein AFV3-109. AFV3-109 is a protein from Acidianus Filamentous Virus 3 with unknown biological function, although structural analysis of AFV3-109 suggests that it could interact with nucleic acids 20 . Among the known slipknotted proteins, AFV3-109 has a relatively simple structure.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 1, the core of AFV3-109 is a β-sheet with five β-strands connected by helices and loops 20 . A clear slipknot conformation is present in AFV3-109 with a knotting loop (colored in yellow, Fig.…”
Section: Introductionmentioning
confidence: 99%